The Effect of Entrepreneurial Self-efficacy and Entrepreneurial Competence on The Entrepreneurial Entry Decision and The Success of Start-up MSMEs in Medan City - Sitinjak, Imelda (Fakultas Ekonomi dan Bisnis, UNTAN, 2019)
One important element in the ASEAN Economic Community (AEC) 2025 blueprint is the strengthening of Small, Medium Enterprises (SMEs). The third largest city in Indonesia, Medan City, has a start-up Micro, Small, and Medium Enterprises (MSMEs) which ranks third in Sumatra itself. The problem is that not all MSMEs in Indonesia can survive or experience growth. So this study aims to determine the effect of entrepreneurial self-efficacy and entrepreneurial competence on entrepreneurial entry decisions and the success of start-up MSMEs in Medan City. The method of determining is the sample using a purposive sampling method, from 100 MSMEs owners. The findings of this study are that entrepreneurial self-efficacy (ESE) has a significant effect on entrepreneurial entry decisions, while entrepreneurial competence is not significant. However, the success of MSME start-ups in Medan is significantly influenced by entrepreneurial competence while ESE is not. The implication of this study is that strong confidence is needed when starting a business, and requires competence to gain business success.